(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate frequency of fetal anomalies in polyhydramniotic patients through antenatal ultrasound in Radiology Department of Pakistan Institute of Medical Sciences (PIMS). Study Design: Cross Sectional Observational study Place and Duration of Study: This study was conducted at the Mother and Child Health (MCH) Centre, Pakistan Institute of Medical Sciences (PIMS), Islamabad from January to December, 2003. Patients and Methods: All women coming for antenatal ultrasound scan during the period January – December 2003 were included in this study. The ultrasound scans were done by the Radiology resident and confirmed by a single consultant radiologist. The data obtained was entered on a proforma. Result: A total of 42(0.79%, n=5260) women were found to have polyhydramnios, out of which 11(26%) had associated fetal anomalies. Among all (11) anomalies detected, there were 5 cases (45.45 %) of anencephaly, 3 cases (27.27 %) of hydrocephalus, one of which had associated meningocele, and 01(9%) case each of omphalocele, spinal anomaly and skeletal dysplasia. 3 (27.27 %) women had concurrent disease. Conclusion: Expart antenatal ultrasound is recommended to assess the presence of polyhydramnios and any associated fetal anomalies. Amniocentesis, glucose tolerance test or HbA1c levels are advisable when the suspicion of associated fetal anomalies is high